2001
DOI: 10.1046/j.1365-2486.2001.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Detecting potential regional effects of increased atmospheric CO2 on growth rates of western juniper

Abstract: Evidence of an atmospheric CO2 fertilization effect on radial growth rates was uncovered by examining climate–growth relationships for seven western juniper tree‐ring chronologies in central Oregon using multiple regression models. Consistent upward trends of the residuals from dendroclimatic models indicated a decreased ability for climate parameters to predict growth with time. Additionally, an assessment was made of whether enhanced growth was detectable under drought conditions, because a major benefit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 42 publications
(63 reference statements)
6
105
0
1
Order By: Relevance
“…Jacoby and D'Arrigo, 1997;Kienast and Luxmoore, 1988;Körner et al, 2005). Furthermore, an improvement of WUE caused by increasing CO 2 concentration has already been suggested in black pine in the Austrian Alps (Leal et al, 2008) and for other species in the Mediterranean (Martínez-Vilalta et al, 2008;Rathgeber et al, 2000) and North America (Knapp et al, 2001). Rathgeber et al (2000) suggested that a combination of warming winters and double CO 2 concentrations enhanced net primary productivity of P. halepensis stands, in accordance with our results of positive trenders.…”
Section: Radial Growth Trends and Their Climatic Driverssupporting
confidence: 89%
See 2 more Smart Citations
“…Jacoby and D'Arrigo, 1997;Kienast and Luxmoore, 1988;Körner et al, 2005). Furthermore, an improvement of WUE caused by increasing CO 2 concentration has already been suggested in black pine in the Austrian Alps (Leal et al, 2008) and for other species in the Mediterranean (Martínez-Vilalta et al, 2008;Rathgeber et al, 2000) and North America (Knapp et al, 2001). Rathgeber et al (2000) suggested that a combination of warming winters and double CO 2 concentrations enhanced net primary productivity of P. halepensis stands, in accordance with our results of positive trenders.…”
Section: Radial Growth Trends and Their Climatic Driverssupporting
confidence: 89%
“…The fact that the ratio of positive trenders were inversely correlated with site productivity and latitude (Fig. 5) agrees with previous studies suggesting that the effect of rising CO 2 concentration would be higher in arid sites (Idso and Idso, 1994;Knapp et al, 2001;Soulé and Knapp, 2006) because the increase in WUE would reduce the drought stress of plants (Morison, 1993), although studies in trees are not conclusive (e.g. Jacoby and D'Arrigo, 1997;Kienast and Luxmoore, 1988;Körner et al, 2005).…”
Section: Radial Growth Trends and Their Climatic Driverssupporting
confidence: 88%
See 1 more Smart Citation
“…The effect of increasing temperature upon plants, in the absence of an increase in precipitation, increases ETP rates and water stress, which together with increasing CO 2 concentrations (Raupach et al, 2007) are likely to affect tree sensitivity and growth. Different authors report different responses to increasing CO 2 concentrations, although in general relative radial growth increases in dry environments due to higher water-use efficiency (WUE) are expected (Hattenschwiler et al, 1997;Knapp et al, 2001;Soulé and Knapp, 2006;Tognetti et al, 2000). However, if ETP increases in Mediterranean ecosystems, water stress could dominate over the CO 2 -induced WUE increase (if any), resulting in important changes in latitudinal and altitudinal shift of species distribution (Benito Garzón et al, 2008).…”
Section: Population Response To Climatementioning
confidence: 99%
“…In old age these trees can assume a "strip-bark" form, characterized by a band of trunk that remains alive and continues to grow after the rest of the stem has died. Such trees are sensitive to higher atmospheric CO 2 concentrations (Graybill and Idso 1993), possibly because of greater water-use efficiency (Knapp et al 2001, Bunn et al 2003 or different carbon partitioning among tree parts (Tang et al 1999). Support for a direct CO 2 influence on tree ring records extracted from "full-bark" trees is less conclusive.…”
Section: Temperature Reconstructionsmentioning
confidence: 99%